Enhancing Stability and Investigating Target Attainment of Benzylpenicillin in Outpatient Parenteral Antimicrobial Therapy: Insights from In Vitro and In Vivo Evaluations - Katharina M. Rentsch; Nina Khanna; Delia Halbeisen; Michael Osthoff (MDPI AG, 2024)
Background/Objective: Narrow-spectrum beta-lactam antibiotics such as benzylpenicillin and flucloxacillin are increasingly used in outpatient parenteral antimicrobial therapy (OPAT) programs to mitigate the adverse effects associated with broad-spectrum antibiotics. These beta-lactams require continuous administration via portable infusion devices during OPAT. However, the use of benzylpenicillin in OPAT requires special consideration because of its limited stability at elevated temperatures. Methods: We tested the benzylpenicillin stability, pH, and degradation of products in elastomeric pumps at different concentrations in saline and in buffered solution containing sodium citrate during a prolonged storage and at high temperatures (seven days at 2-8 °C followed by 24 h at 37 °C). Additionally, drug concentrations during intermittent bolus infusion and during OPAT were determined in five patients. The concentrations and degradation products of benzylpenicillin were measured using liquid chromatography mass spectrometry (LC-MS/MS). Results: Unbuffered benzylpenicillin solutions that were already degraded during refrigerator storage and analyte concentration were not measurable after 8 days. The stability of the buffered solutions was acceptable at all three of the tested concentrations (97.6 ± 1.3%, 96.3 ± 0.8%, and 94.9 ± 1.1% for 10 Mio IU, 20 Mio IU, and 40 Mio IU of benzylpenicillin). The stability was influenced by benzylpenicillin concentration, and several breakdown products were identified. Benzylpenicillin concentrations were measured in five patients during OPAT and ranged from 7.2 to 60 mg/L. Conclusions: Benzylpenicillin buffered with sodium citrate is a safe and convenient option for use in continuous infusions during OPAT and should be favored over broad-spectrum antibiotics. Therapeutic drug monitoring data indicate sufficient to high plasma levels when patients received benzylpenicillin as continuous infusions.